Caspase-9 inhibition confers stronger neuronal and vascular protection compared to VEGF neutralization in a mouse model of retinal vein occlusion - Avrutsky, Maria I.; Chen, Claire W.; Lawson, Jacqueline M.; Snipas, Scott J.; Salvesen, Guy S.; Troy, Carol M. (Frontiers in Neuroscience, 2023)
Purpose: Retinal vein occlusion (RVO) is a sight-threatening condition typically treated with intravitreal injection of vascular endothelial growth factor (VEGF) antagonists. Treatment response to anti-VEGF therapies is highly variable, with poor visual outcomes and treatment response in patients with significant retinal nonperfusion following RVO. Recently, caspase-9 has been identified as a potent regulator of edema, gliosis, and neuronal dysfunction during acute retinal hypoxia. The purpose of this study was to compare the therapeutic effect of caspase-9 inhibition against VEGF-neutralization in an established mouse model of RVO. Methods: Adult male C57Bl/6J mice were randomized to induction of RVO and treatment with either vehicle, intravitreal injection of anti-VEGF antibody, topical administration of a selective caspase-9 inhibitor (Pen1-XBir3), or a combination therapy. Animals were followed on days 1, 2, and 8 after RVO with fundus retinal imaging, and with optical coherence tomography (OCT) to capture retinal swelling, capillary nonperfusion (measured by disorganization of retinal inner layers, (DRIL), hyperreflective foci (HRF), and retinal atrophy. Focal electroretinography (ERG) measurements were performed on day 7. Histology was performed on retinal sections from day 8. Results: Both VEGF neutralization and caspase-9 inhibition showed significant retinal protection from RVO compared to vehicle treatment arm. Retinal reperfusion of occluded veins was accelerated in eyes receiving caspase-9 inhibitor, but not significantly different from vehicle in the anti-VEGF group. Retinal edema was suppressed in all treatment groups, with approximately 2-fold greater edema reduction with caspase-9 inhibition compared to VEGF neutralization. HRF were reduced similarly across all treatment groups compared to vehicle. Retinal detachment was reduced only in eyes treated with caspase-9 inhibitor monotherapy. Caspase-9 inhibition reduced retinal atrophy and preserved ERG response; VEGF neutralization did not prevent neurodegeneration following RVO. Conclusion: Caspase-9 inhibition confers stronger neuronal and vascular protection compared to VEGF neutralization in the mouse laser-induced model of RVO.